Norwegian physicians' knowledge of and opinions about evidence-based medicine: cross-sectional study. - Lidziya Vanahel Ulvenes (Public Library of Science (PLoS), 2009)
Objective To answer five research questions: Do Norwegian physicians know about the three important aspects of EBM? Do they use EBM methods in their clinical practice? What are their attitudes towards EBM? Has EBM in their opinion changed medical practice during the last 10 years? Do they use EBM based information sources? Design Cross sectional survey in 2006. Setting Norway. Participants 966 doctors who responded to a questionnaire (70% response rate). Results In total 87% of the physicians mentioned the use of randomised clinical trials as a key aspect of EBM, while 53% of them mentioned use of clinical expertise and only 19% patients' values. 40% of the respondents reported that their practice had always been evidence-based. Many respondents experienced difficulties in using EBM principles in their clinical practice because of lack of time and difficulties in searching EBM based literature. 80% agreed that EBM helps physicians towards better practice and 52% that it improves patients' health. As reasons for changes in medical practice 86% of respondents mentioned medical progress, but only 39% EBM. Conclusions The results of the study indicate that Norwegian physicians have a limited knowledge of the key aspects of EBM but a positive attitude towards the concept. They had limited experience in the practice of EBM and were rather indifferent to the impact of EBM on medical practice. For solving a patient problem, physicians would rather consult a colleague than searching evidence based resources such as the Cochrane Library.